The impact of COVID‐19 on food systems, safety, and security—a symposium report. Issue 1 (28th August 2020) - Cable, Jennifer; Jaykus, Lee‐Ann; Hoelzer, Karin; Newton, John; Torero, Maximo
Abstract: Our food systems depend on complex interactions between farmers and food producers, local and federal governments, and consumers. Underlying these interactions are economic, environmental, and societal factors that can impact the types of food available, access to food, affordability, and food safety. The recent SARS‐CoV‐2 global pandemic has affected multiple aspects of our food systems, from federal governments' decisions to limit food exports, to the ability of government agencies to inspect food and facilities to the ability of consumers to dine at restaurants. It has also provided opportunities for societies to take a close look at the vulnerabilities in our food systems and reinvent them to be more robust and resilient. For the most part, how these changes ultimately affect the safety and accessibility of food around the world remains to be seen.